Use of structural bone allograft in revision hip arthroplasty for massive acetabular defect: A systematic review and meta‐analysis - Pietro Cimatti; Nicolandrea Del Piccolo; Alessandro Mazzotta; Benedetta Dallari; Enrico Pennello; Dante Dallari (Journal of Experimental Orthopaedics)
ABSTRACT Purpose Managing substantial acetabular defects during revision total hip arthroplasty (rTHA) poses significant challenges, with a range of techniques available and ongoing discussions regarding their efficacy. This meta‐analysis aimed to assess the failure rates associated with Paprosky type III and American Academy of Orthopaedic Surgeons (AAOS) types III–IV acetabular defects treated with structural allografts in conjunction with cemented cups, cementless cups, or reinforcement devices. Methods A systematic review was performed utilising PubMed/MEDLINE, EMBASE, and the Cochrane Database of Systematic Reviews to identify pertinent studies published from January 1980 to 1 April 2024. The search employed terms related to acetabular impaction bone grafting, rTHA, and associated techniques. The main outcome measure was the implant failure rate over an 8‐year period. Results Twenty‐eight studies met the established inclusion criteria, covering three therapeutic approaches: (1) structural allograft with a cemented cup (four studies), (2) structural allograft with a cementless cup (10 studies), and (3) structural allograft with reinforcement devices (21 studies). The overall 8‐year implant failure rate was found to be 16% (95% CI, 11%–21%), with significant differences noted among the treatment modalities (p = 0.017). The failure rate was lowest for reinforcement devices (12%) and highest for cemented cups (30%). The predominant failure mechanism was aseptic loosening (68.9%), followed by infection (20.3%) and dislocation (10.8%). Rates of aseptic loosening were greater with cemented cups compared to cementless cups and reinforcement devices (19% vs. 13% and 6%, respectively; p = 0.023). Conclusions Structural allografts combined with reinforcement devices yield favourable outcomes for managing large acetabular defects during revision THA, demonstrating significantly lower failure rates compared to other techniques. The addition of reinforcement devices substantially reduces the risk of implant failure. Level of Evidence Level III.